Prolonged reduction of leukocyte membrane-associated Dectin-1 levels following beta-glucan administration. - Ozment-Skelton, T; Goldman, M; Gordon, S; Brown, G; Williams, D (2006)
Dectin-1 is the primary pattern recognition receptor for fungal glucans. Dectin-1 mediates the internalization and biological response to glucans. We examined the effect of i.v. or i.p. glucan phosphate (GP) administration on Dectin-1 membrane expression in murine peripheral blood leukocytes, splenocytes, bone marrow, and peritoneal cells from 3 h to 10 days after injection. Circulating leukocytes were also examined for uptake and internalization of glucans from the blood. Fluorescent-labeled GP was taken up from the systemic circulation by circulating peripheral leukocytes, splenocytes, and peritoneal cells. Following internalization, glucan colocalized with Dectin-1 in an intracellular vesicle. A single parenteral injection of GP resulted in a significant reduction (approximately 33-85%) in peripheral leukocyte membrane-associated Dectin-1 positivity that lasted for up to 7 days. The loss of leukocyte membrane-associated Dectin-1 after GP administration was primarily due to decreased levels of Dectin-1 on neutrophil and monocyte membranes with no significant changes in the percentage of neutrophils or monocytes circulating in the blood. Administration of control carbohydrate polymers, i.e., mannan or pullulan, which are not ligands for Dectin-1, did not decrease Dectin-1 leukocyte positivity, indicating that the effect on Dectin-1 is specific to glucans. In fact, mannan administration increased leukocyte Dectin-1 positivity, thus demonstrating a differential effect on leukocyte Dectin-1, compared with GP. We conclude that systemic administration of GP has a specific and prolonged effect on loss of leukocyte membrane Dectin-1 positivity. These data may have important implications for developing dosing regimens for immunomodulatory carbohydrates.